1998
DOI: 10.1016/s0029-7844(97)00587-5
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Intrapartum Ampicillin and Prevention of Vertical Transmission of Group B Streptococcus

Abstract: When the time between the start of ampicillin prophylaxis and delivery is at least 2 hours, vertical transmission of group B streptococcus is minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 23 publications
3
76
0
13
Order By: Relevance
“…Duration of IAP of 4 hours of beta-lactam antibiotics has been shown to be highly effective in preventing vertical transmission of GBS and GBS EOD [18,124,126,131,132]. Even though not ideal, duration of IAP 2 hours can provide acceptable coverage [131,[133][134][135].…”
Section: Intrapartum Antibiotic Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Duration of IAP of 4 hours of beta-lactam antibiotics has been shown to be highly effective in preventing vertical transmission of GBS and GBS EOD [18,124,126,131,132]. Even though not ideal, duration of IAP 2 hours can provide acceptable coverage [131,[133][134][135].…”
Section: Intrapartum Antibiotic Prophylaxismentioning
confidence: 99%
“…Even though not ideal, duration of IAP 2 hours can provide acceptable coverage [131,[133][134][135]. In cases of less than acceptable coverage (52 hours) the neonatologist should be informed.…”
Section: Intrapartum Antibiotic Prophylaxismentioning
confidence: 99%
“…10,25,26 En este sentido, poder identificar grupos de embarazadas con mayor riesgo de infección aumenta la posibilidad de una mejor vigilancia perinatal y, por lo tanto, de prevenir, diagnosticar y tratar oportunamente este tipo de infección. 8,11 De acuerdo con lo anterior y con base en los resultados de este estudio, las acciones encaminadas a la prevención y control de la infección por SGB se deberían dirigir a la atención de la población de mayor riesgo de colonización con el fin de disminuir las probabilidades de infección y la transmisión perinatal de SGB.…”
Section: Discussionunclassified
“…21 Asimismo, la letalidad de la ENT suele abarcar a 55% de los casos, aunque se ha demostrado que un diagnóstico y tratamiento oportunos pueden disminuir dicha letalidad entre 13 y 37%. [25][26][27] Si bien el papel de los factores obstétricos ha sido ampliamente analizado en la mayoría de los trabajos sobre colonización materna por SGB, 2,5,8 el papel de los factores demográficos y socioeconómicos ha sido poco evaluado, no obstante la existencia de estudios que evidencian que factores como la edad 17 y el grupo étnico 6,15 pueden jugar un papel importante en la infección por SGB. Aun cuando en esos estudios no se explican los mecanismos por los cuales esos factores podrían incrementar la tasa de colonización por SGB sí sugieren que ésta podría estar vinculada a condiciones de pobreza y marginación, lo que, a su vez, se podría constituir en un elemento importante para identificar grupos de alto riesgo entre la población general.…”
Section: Objetivo Estimar La Prevalencia De Colonización Por Streptounclassified
“…There is evidence that benzylpenicillin levels in cord blood exceed the minimum inhibitory concentration for GBS as early as 1 hour after maternal administration 51 but it is not known how this relates to neonatal colonisation or disease. There is also evidence that giving penicillin for 2 hours before delivery reduces neonatal colonisation 52,53 but evidence from 2013 54 suggests that 4 hours of penicillin is more effective than 2 hours at reducing the risk of EOGBS disease. Amoxicillin is an alternative but the Cochrane review 7 found no difference between amoxicillin and benzylpenicillin and thus, the narrower spectrum antibiotic is preferred.…”
mentioning
confidence: 99%